(untitled) (The Review of Diabetic Studies, 2025)
Objectives: To investigate the associations between central and peripheral adiposity, as measured by skinfold thickness, and blood pressure indices in sedentary female educators, independent of age and body mass index (BMI). Methods: A cross-sectional study of 120 sedentary female educators (ages 32–50) from an Indian school district collected data on height, weight, BMI, blood pressure (systolic and diastolic), and skinfold thickness at four sites (suprailiac, subscapular, biceps, and triceps). Pearson correlation coefficients were used to examine the relationships between adiposity measures and blood pressure. Multiple linear regression models were used to assess the independent effects of skinfold sites on blood pressure, while adjusting for age and BMI. Results: Participants had a mean age of 42.2 years (SD = 4.7) and a mean BMI of 26.5 kg/m² (SD = 4.7). Central skinfolds (suprailiac, subscapular) showed the strongest positive correlations with both systolic and diastolic blood pressure (r = .35–.32, p < .01). Regression analyses revealed that suprailiac (β = 0.65, p = .002) and subscapular (β = 0.50, p = .008) skinfolds were significant independent predictors of systolic and diastolic blood pressure, respectively, even after controlling for age and BMI. Conclusions: Central adiposity, measured by skinfolds, predicts blood pressure in sedentary female educators. These findings emphasise the need to assess regional fat distribution for cardiovascular risk stratification and targeted intervention in this group.